Impact peak force measurement of potato - Weigang Deng; Chunguang Wang; Shengshi Xie (International Journal of Food Properties, 2020)
To analyze the influencing factors of impact force on potatoes, a mathematical model between the impact peak force$${F_m}$$, the potato mass $$m$$ and the drop height $$h$$ was established as $${F_m} =km\sqrt h$$. A single-factor impact test was carried out, and the models for $${F_m}$$, $$m$$ and $$h$$ were presented as $${F_m}{\rm{ = 318}}{\rm{.36}}m + 9.8$$ and $${F_m}{\rm{ = 306}}{\rm{.56}}\sqrt h$$. Taking the combination form $$m\sqrt h$$ of $$m$$ and $$h$$ as the test factor, the $${F_m}$$ of two potato varieties, namely, Xiabodi and Gaoyuanhong, were tested under the impact materials of steel, steel-soft plastic, steel-rubber and steel-leather. The relationships between $${F_m}$$ and $$m\sqrt h$$ were all $${F_m} = {k_1}m\sqrt h$$ under the four types of impact materials by the regression analysis of the test results. The range of $${k_1}$$ was from 980.9 to 1395.7. The effect of potato variety on $${F_m}$$ was analyzed. The results showed that under the same conditions, the $${F_m}$$ of Xiabodi was 8.03 N smaller than that of Gaoyuanhong on average, which indicated that Xiabodi had a better tolerance to impact force. The effect of impact material on $${F_m}$$ was analyzed. The results showed that $${F_m}$$ with steel, steel-leather, steel-rubber and steel-soft plastic decreased in turn, and the average difference between the maximum and minimum value of $${F_m}$$ was 16.6 N.